The Representation of Political Memes on Social Media X (Twitter): A Semiotic Analysis of Popular Culture Products - Pranata, Angga; Widyatama, Rendra (Communications, 2025)
Memes are popular cultural products that has gained significant influence in the political communication, particularly among younger demographics. With their ability to combine textual and visual elements, memes have become an effective instrument for conveying socio-political aspirations and critiques in the digital age. This study utilizes Barthes' semiotic theory to analyze the denotative and connotative meanings of elements within political memes. The research employs a descriptive qualitative approach to provide an in-depth description of the construction of political narratives. Data collection was conducted through two principal methods: literature analysis and content uploads on platform X (Twitter) using the purposive Search Advanced Technology (SAT). The findings show that political memes represent public dissatisfaction with political actors, government elites, and policymakers, making them a strategic informal communication instrument. The study successfully identifies national and international political narratives and situations. Meme products have simplified political narratives, attracted public attention, stimulated critical discussions, and built collective awareness. In conclusion, political memes on social media play a crucial role in representing modern political dynamics and the centralization of media in shaping public perception, as well as facilitating political discourse. By emphasizing the relevance of modern digital culture, this study pioneers in explaining the role of memes as a product of popular culture. However, this research is limited to platform X (Twitter), and cross-platform studies with a mixed-methods approach are necessary for a more holistic understanding of memes in advanced political discourse. This finding contributes to the study of political communication and contemporary digital culture.